Gesture’s Neural Language - Andric, Michael; Small, Steven L. (Frontiers in Psychology, 2012)
When people talk to each other, they often make arm and hand movements that accompany what they say. These manual movements, called “co-speech gestures,” can convey meaning by way of their interaction with the oral message. Another class of manual gestures, called “emblematic gestures” or “emblems,” also conveys meaning, but in contrast to co-speech gestures, they can do so directly and independent of speech. There is currently significant interest in the behavioral and biological relationships between action and language. Since co-speech gestures are actions that rely on spoken language, and emblems convey meaning to the effect that they can sometimes substitute for speech, these actions may be important, and potentially informative, examples of language–motor interactions. Researchers have recently been examining how the brain processes these actions. The current results of this work do not yet give a clear understanding of gesture processing at the neural level. For the most part, however, it seems that two complimentary sets of brain areas respond when people see gestures, reflecting their role in disambiguating meaning. These include areas thought to be important for understanding actions and areas ordinarily related to processing language. The shared and distinct responses across these two sets of areas during communication are just beginning to emerge. In this review, we talk about the ways that the brain responds when people see gestures, how these responses relate to brain activity when people process language, and how these might relate in normal, everyday communication.